2017
DOI: 10.1097/rct.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrium Measurements via Computed Tomography Pulmonary Angiogram as a Predictor of Diastolic Dysfunction

Abstract: PURPOSE Left atrium (LA) enlargement on echocardiography may be an indicator of diastolic dysfunction (DD). It is not well known if computed tomography pulmonary angiography (CTPA) can detect DD. METHODS 127 patients who underwent both CTPA and echo within 48 hours were analyzed retrospectively. LA diameters from CTPA were correlated with echo and evaluated against degrees of DD. CTPA pulmonary artery (PA)/Aorta ratio was analyzed as a tool to detect pulmonary hypertension. RESULTS 42% of patients had DD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…In comparison diameter measurements of the LV, RV, and LA as well as ratios of diameter measurements showed lower diagnostic performances to diagnose HF. For these parameters, LA diameter had the highest AUC, which is compatible with previous studies [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In comparison diameter measurements of the LV, RV, and LA as well as ratios of diameter measurements showed lower diagnostic performances to diagnose HF. For these parameters, LA diameter had the highest AUC, which is compatible with previous studies [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…One reader (C.R., 1 year of experience in radiology) performed diameter measurements of the LV, RV, and left atrium (LA) as previously described [ 21 , 22 ]. LV and RV diameters were measured at their widest point at the midventricular level, on the same CT axial image (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study not only provides confirmatory evidence for the diagnostic accuracy of LA volume in a different institution and patient cohort but also demonstrates its superiority compared to LA axial anteroposterior diameter in an intra-individual comparison. LA anteroposterior diameter is the most widely used LA measurement in clinical practice and PH research in both echocardiography and CT according to international recommendations and literature [ 7 , 19 , 27 – 30 ]. Previous studies reported AUC values of 0.71–0.83 for identification of group 2 PH by LA anteroposterior diameter, compared to 0.83 in our study cohort [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…LV and RV diameters were measured perpendicular to the interventricular septum on the slice on which the respective ventricle appeared largest [18]. LA diameter was determined as the largest anterior-posterior-diameter on the slice in the middle 50% of the craniocaudal extension of the left atrium [19]. RA diameter was measured as the largest diameter parallel to the tricuspid valve plane, excluding right atrial appendage and coronary sinus [20].…”
Section: Image Analysismentioning
confidence: 99%